Hubungan antara Resiliensi dan Self-Efficacy dengan Burnout Syndrome pada Perawat Ruang Rawat Inap Rumah Sakit - Sajodin; Perla Yualita (Faletehan Health Journal, 2025)
As the largest professional health workforce in Indonesia, nurses face high demands and responsibilities in hospitals, making them vulnerable to burnout syndrome. Resilience and self-efficacy are considered important factors that may mitigate this risk. This study aimed to analyze the relationship of resilience, self-efficacy, and burnout syndrome among nurses. This study used a descriptive correlational design with a cross-sectional approach. The population consisted of 140 inpatient nurses, from which a sample of 100 respondents was selected using stratified random sampling with a 5% significance level. The majority of nurses had high levels of resilience (58%) and self-efficacy (55%). However, a high level of burnout syndrome was also found in 55% of the nurses. The Spearman Rank correlation test revealed no significant relationship between resilience and burnout syndrome (p=0.968), nor between self-efficacy and burnout syndrome (p=0.921). No relationship was found between resilience, self-efficacy, and burnout syndrome in the nurse population of this study. Further research is recommended to explore other contributing factors or to investigate this phenomenon in different contexts, such as among nurses in the education sector.